Academic Stress Influences Periodontal Health Condition and Interleukin-1 beta Level - Kuswandani, Sandra O.; Masulili, Sri LC.; Soedarsono, Nurtami; Kemal, Yulianti (Journal of Dentistry Indonesia, 2014)
Stress is a risk factor for periodontal disease, causing increase levels of interleukin-1 beta that involve in periodontal destruction. Objective: To analyze the relationship between academic stress in residency program students conditions and levels of interleukin-1 beta in gingival crevicular fluid. Methods: Thirty eight subjects filled the questionnaire of Graduate Dental Environtmental Stress (GDES), periodontal examination and samples of gingival crevicular fluid were tested for interleukin-1 beta with the Enzyme-linked Immunosorbent Assay (ELISA) test. Results: There were significant differences between academic stress to periodontal tissue in oral hygiene (p=0.038), bleeding on probing index (p=0.02), but no significant differences in pocket depth and loss of attachment (p=0.972). There were significant differences between academic stress to levels of interleukin-1 beta (p=0.03), but no significant differences between levels of interleukin-1 beta to periodontal tissue in oral hygiene (p=0.465), bleeding on probing index (p=0.826), pocket depth (p=0.968), and loss of attachment (p=0.968). Conclusion: Academic stress influences the periodontal risk factor and level of interleukin-1 beta.